Empowering Teachers to Design 6C-Integrated Project-Based Learning for 21st-Century Classrooms (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Teachers' poor ability to connect abstract mathematical concepts with contextual phenomena is a major challenge in secondary schools. Consequently, student engagement is low, 21st-century skills are poorly developed, and learning innovations are rare. This situation demands solutions that are not merely theoretical but also practical, contextual, and easy to implement. This community service activity aims to increase the capacity of partner teachers in designing, implementing, and evaluating project-based mathematics learning that integrates six 21st-century competencies (Critical Thinking, Creativity, Collaboration, Communication, Citizenship, and Character). The proposed solution is the implementation of the 6Cs-based Mathematics Learning Project Design Model, which combines 21st-century pedagogical principles with a Project-Based Learning (PjBL) approach. The implementation method included: outreach, teacher training on the 6Cs and PjBL concepts, intensive mentoring in project design and implementation, and evaluation. The results showed that the training went smoothly and received a positive response. Participants participated in all stages of the activity, and mathematics teachers were able to develop learning projects according to what was explained during the training. During the implementation process, subjects were also able to implement and receive positive responses in learning. This was evident in the improvement in students' pretest and posttest scores. Activity data indicates an increase in teacher competency after they received training and mentoring, with average scores on several dimensions increasing to 3.44–3.50. The initial impact on student learning achievement is also evident in the increase in the average score from 78.20 to 80.75 and the lowest score from 60 to 70. These findings underscore that the implementation of Project-Based Learning combined with 6C skills not only strengthens teacher readiness but also plays a role in improving student learning outcomes in a more contextual and meaningful way.